What Does That Mean? Complementizers and Epistemic Authority - Tollan, Rebecca; Palaz, Bilge (Open mind (Cambridge, Mass.), 2024)
A core goal of research in language is to understand the factors that guide choice of linguistic form where more than one option is syntactically well-formed. We discuss one case of optionality that has generated longstanding discussion: the choice of either using or dropping the English complementizer in sentences like . Existing psycholinguistic analyses tie -usage to production pressures associated with sentence planning (Ferreira & Dell, ), avoidance of ambiguity (Hawkins, ), and relative information density (Jaeger, ). Building on observations from cross-linguistic fieldwork, we present a novel proposal in which English can serve to mark a speaker’s “epistemic authority” over the information packaged within the embedded clause; that is, it indicates that the speaker has more knowledge of the embedded proposition compared with their addressee and thus has a perspective that they believe their addressee doesn’t share. Testing this proposal with a forced-choice task and a series of corpus surveys, we find that English is keyed to the use of embedded speaker (first-person) subject pronouns and occurs in sentences containing newsworthy information. Our account of -optionality takes into account why is associated with both (i) a dense information signal and (ii) semantic-pragmatic content, as well as extending to cases of non-optionality in subject/sentence-initial clauses (e.g., * ) and fragment answers (e.g., * ), where is required.